(untitled) (gjstudies, 2019)
This research paper investigates the evolving and increasingly complex ethical landscape confronting accounting professionals in contemporary business environments. Moving beyond traditional discussions of fraud and compliance, this study adopts a novel, cross-disciplinary frameworkthat integrates principles from behavioral economics, organizational psychology, and digital ethicsto analyze ethical dilemmas. The central research question explores how digital transformation, algorithmic decision-making, and new organizational structures are reshaping the fundamental natureof ethical challenges in accounting, creating novel tensions between technical accuracy, professionaljudgment, and societal impact. The methodology employs a qualitative, multi-case study analysis of ethical incidents reported within professional bodies and regulatory filings over a five-yearperiod, supplemented by in-depth interviews with practicing accountants across diverse sectors.This approach allows for the identification of emergent, non-traditional ethical dilemmas that arepoorly captured by existing codes of conduct. The results reveal a significant paradigm shift: ethical challenges are increasingly systemic and embedded within technological systems and businessmodels, rather than stemming from individual malfeasance. Key findings identify three novel ethical domains: (1) the ’ethics of opacity’ in black-box financial algorithms, (2) responsibility fordownstream societal consequences of financial reporting in areas like environmental, social, andgovernance (ESG) metrics, and (3) ethical conflicts arising from the accountant’s dual role as datasteward and strategic advisor in data-driven organizations. The study concludes that existing ethicalframeworks, largely designed for a pre-digital era, are insufficient. It contributes original insightsby proposing a dynamic, principle-based ethical model that emphasizes proactive ethical reasoning,technological literacy, and systems thinking as core professional competencies, rather than static rulecompliance. This research provides a foundational re-conceptualization of accounting ethics for the21st century.